CEMAC : Deepening Regional Integration to Advance Growth and Prosperity - World Bank (World Bank, Washington, DC, 2019)
The Central African Economic and Monetary Community (CEMAC), which consists of Cameroon, the Central African Republic, Chad, the Republic of Congo, Equatorial Guinea and Gabon, is one of the oldest regional groupings in Africa. The main objectives for achieving this are: (i) the creation of a fully functional and effective customs union, (ii) the establishment of a robust system of macroeconomic surveillance, and (iii) the harmonization of sectoral policies and legal frameworks that will create a common market for goods, capital, and services.Despite this ambitious vision, regional integration in the CEMAC zone remains shallow.The oil price shock of 2014-15 severely affected the six CEMAC economies and promoted re-commitment to deepening regional integration.At the regional level, the PREF also aims to: (i) improve the coordination of public financial management (PFM) and fiscal policy; (ii) accelerate regional integration through improvements to the regional economic plan; (iii) improve the business climate; (iv) increase economic diversification; (v) enhance monetary policy transmission mechanisms; and (vi) improve prudential banking supervision.CEMAC is right to focus on reforms to deepening regional integration as a driver of growth.The objective of this Regional Study on CEMAC is to support policy makers in CEMAC in efforts to strengthen regional integration to support economic growth and to reduce the need for economic adjustment. The Regional Study focuses mainly on what can be done at the regional level to support regional integration, macro-stability and long-term growth in the CEMAC area; as such, the Regional Study aims to complement country-specific policies and initiatives to support macro-stabilization, economic development and integration.